(untitled) - Hammond, Richard T. (Singapore, 2001)
This title presents a series of interviews in which natural objects such as an electron, a black hole, a galaxy, and even the vacuum itself, reveal their innermost secrets - not only what they are but also how they feel. A hydrogen atom tells us about quantum mechanics and why we live in a non-deterministic world; a black hole explains curved space and naked singularities; and a uranium atom talks of its life on a meteor, its tremendous collision with Earth, and properties of radioactivity - all while grappling with its own mortality. A neutron star gives a personal account of its creation and goes on to discuss quasars and other extraordinary astronomical objects, while an iron atom describes its birth in a remote supernova explosion and its series of adventures on Earth, from its early use in wrought iron processes to its time in a human body, and then to its latest misadventures.
Keywords: Vật lý,Physics; Công trình phổ biến,Popular works